SHORT VS LONG COURSE RADIOTHERAPY IN RECTAL CANCER: ACUTE TOXICITY AND OUTCOMES FROM A SINGLE-CENTRE COHORT" - Viraj Modi; Nikhil Bathija; Ankita Parikh; Jayesh Kumar Singh; Vinay Shivhare; Satyajit Rath (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Short-course radiotherapy (SCRT) and long-course chemoradiation (LCRT) are accepted neoadjuvant options in locally advanced rectal cancer (LARC), yet real-world comparative data on acute toxicity and early surgical quality are limited. Methods: This single-centre randomized two-arm cohort compared SCRT (25 Gy/5 fractions with delayed surgery) versus LCRT (45 Gy/25 fractions with concurrent capecitabine plus 5.4 Gy boost). Acute toxicities were graded by RTOG/WHO criteria. The primary endpoint was clinically relevant acute toxicity; secondary endpoints included sphincter preservation, margin status, postoperative complications, pathological response, and early distant metastasis. Analyses were intention-to-treat using Fisher’s exact tests with 95% CIs. Results: Thirty-nine patients were enrolled (SCRT = 16; LCRT = 23). Clinically relevant acute toxicities were markedly lower with SCRT: no ≥G2 skin events (0% vs 69.6%), fewer GI/proctitis ≥G2 (31.3% vs 87.0%), and no hematologic ≥G2 (0% vs 13.0%). Sphincter preservation (46.7% vs 40.9%), R0 resection rates (87.5% vs 87.0%), margins, and 30-day complications were comparable. Pathologic CR occurred in 10.3% overall. Early distant metastasis was 0% after SCRT vs 13.0% after LCRT. Conclusions: Compared with LCRT, SCRT with consolidation chemotherapy and delayed surgery produced substantially lower acute skin, gastrointestinal, and hematologic toxicity with comparable surgical quality metrics, supporting SCRT as a tolerable, resource-efficient neoadjuvant strategy warranting confirmation in larger prospective cohorts with longer follow-up and patient-reported outcomes.